Formulasi dan Evaluasi Sediaan Lotion Pencegah Photo Aging Ekstrak Etanol Buah Ficus racemosa L. - Suryani, Novia; Ernita, Nevi; Hidayanti, Baiq Rauhil; Damalianti, Yulia (ALCHEMY:Journal of Chemistry, 2024)
This study aims to determine the potential of ethanol extract of elo fruit (Ficus racemosa L.) as a photo-aging lotion preparation. Photo aging preventive lotion formulation was made in 5 variations. Each formulation was tested for characterization of physical properties in the form of pH test, diameter of spreadability, homogeneity, and stability through 3 cycles. Ethanol extract of elo fruit was obtained using a simple maceration method in 96% ethanol solvent. Based on the results of the qualitative phytochemical test, the ethanol extract of elo fruit contains flavonoid and tannin compounds. The pH test results show that the lotion formulation has a range of 7.27 - 7.65. The results of the diameter of spreadability using a weight of 200 g, 400 g, and 600 g obtained a diameter in the range of 2.16 cm - 3.70 cm. Each lotion formulation has good homogeneity. The results of the stability test against 4oC and room temperature showed no changes in aroma, color, and texture that occurred in each lotion formulation F1 - F5.